Advertisement Remove all ads

Solve `3tan^(-1)X + Cot^(-1) X = Pi` - Mathematics

Solve `3tan^(-1)x + cot^(-1) x = pi`

Advertisement Remove all ads

Solution

`3tan^(-1) x +  cot^(-1) x = pi`

`:. 2tan^(-1) x + tan^(-1) x + cot^(-1) = pi`

`:. 2tan^(-1) x + pi/2 = pi`

`2tan^(-1) x = pi = pi/2`

`tan^(-1) (x) = pi/2 - pi/4`

`x= tan (pi/2 - pi/4)`

x = 1

Concept: Inverse Trigonometric Functions - Inverse Trigonometric Functions - Principal Value Branch
  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×